Interconnected robotic platforms inform deep-sea ecological restoration trends - Ivan Masmitja; Narcís Palomeras; Daniel M. Toma; Nixon Bahamon; Matias Carandell; José A. García del Arco; Damianos Chatzievangelou; Marta Real; Antoni Sánchez-Márquez; Gerard Batet; Pau Vial; Francisco Bonin-Font; et al. (Marine Pollution Bulletin, 2025)

Enhancing fish community monitoring at a cabled observatory by combining environmental DNA and imaging analysis - Maddalena Tibone; Marco Francescangeli; Sergio Stefanni; Jacopo Aguzzi; Bernadette O'Neill; Joaquin Del Rio; Daniel Mihai Toma; Luca Mirimin (Journal of Fish Biology, 2025)
Cabled multiparametric observatories are sustaining ecological monitoring by collecting long‐term real‐time biological and environmental data. Here, we investigated fish communities by sampling environmental DNA (eDNA) over 4 days near the multiparametric cabled video‐observatory OBSEA (Northwestern Mediterranean Sea). The multi‐marker eDNA metabarcoding approach resulted in an increased species detection and helped provide a more comprehensive view of the local fish community when combined with imaging data. These results underline the potential of omics methods in long‐term monitoring of economically and ecologically important fish species.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

10-Years of imagery from a cabled-observatory reveals a decreasing trend in coastal fish biodiversity - Marco Francescangeli; Jacopo Aguzzi; Damianos Chatzievangelou; Morane Clavel-Henry; Nixon Bahamon; Nathan J. Robinson; Enoc Martínez; Albert Garcia Benadí; Daniel M. Toma; Joaquin Del Rio (Science of The Total Environment, 2025)

Advancing fishery-independent stock assessments for the Norway lobster (Nephrops norvegicus) with new monitoring technologies - Jacopo Aguzzi; Damianos Chatzievangelou; Nathan J. Robinson; Nixon Bahamon; Alan Berry; Marc Carreras; Joan Batista Company; Corrado Costa; Joaquin del Rio Fernandez; Ahmad Falahzadeh; Spyros Fifas; Sascha Flögel; et al. (Frontiers in Marine Science, 2022)
The Norway lobster, Nephrops norvegicus , supports a key European fishery. Stock assessments for this species are mostly based on trawling and UnderWater TeleVision (UWTV) surveys. However, N. norvegicus are burrowing organisms and these survey methods are unable to sample or observe individuals in their burrows. To account for this, UWTV surveys generally assume that “1 burrow system = 1 animal”, due to the territorial behavior of N. norvegicus . Nevertheless, this assumption still requires in-situ validation. Here, we outline how to improve the accuracy of current stock assessments for N. norvegicus with novel ecological monitoring technologies, including: robotic fixed and mobile camera-platforms, telemetry, environmental DNA (eDNA), and Artificial Intelligence (AI). First, we outline the present status and threat for overexploitation in N. norvegicus stocks. Then, we discuss how the burrowing behavior of N. norvegicus biases current stock assessment methods. We propose that state-of-the-art stationary and mobile robotic platforms endowed with innovative sensors and complemented with AI tools could be used to count both animals and burrows systems in-situ , as well as to provide key insights into burrowing behavior. Next, we illustrate how multiparametric monitoring can be incorporated into assessments of physiology and burrowing behavior. Finally, we develop a flowchart for the appropriate treatment of multiparametric biological and environmental data required to improve current stock assessment methods.

Assessing the Image Concept Drift at the OBSEA Coastal Underwater Cabled Observatory - Ennio Ottaviani; Marco Francescangeli; Nikolla Gjeci; Joaquin del Rio Fernandez; Jacopo Aguzzi; Simone Marini (Frontiers in Marine Science, 2022)
The marine science community is engaged in the exploration and monitoring of biodiversity dynamics, with a special interest for understanding the ecosystem functioning and for tracking the growing anthropogenic impacts. The accurate monitoring of marine ecosystems requires the development of innovative and effective technological solutions to allow a remote and continuous collection of data. Cabled fixed observatories, equipped with camera systems and multiparametric sensors, allow for a non-invasive acquisition of valuable datasets, at a high-frequency rate and for periods extended in time. When large collections of visual data are acquired, the implementation of automated intelligent services is mandatory to automatically extract the relevant biological information from the gathered data. Nevertheless, the automated detection and classification of streamed visual data suffer from the “concept drift” phenomenon, consisting of a drop of performance over the time, mainly caused by the dynamic variation of the acquisition conditions. This work quantifies the degradation of the fish detection and classification performance on an image dataset acquired at the OBSEA cabled video-observatory over a one-year period and finally discusses the methodological solutions needed to implement an effective automated classification service operating in real time.

Long-Term Monitoring of Diel and Seasonal Rhythm of Dentex dentex at an Artificial Reef - Marco Francescangeli; Valerio Sbragaglia; Joaquin del Rio Fernandez; Enric Trullols; Josefina Antonijuan; Immaculada Massana; Joana Prat; Marc Nogueras Cervera; Daniel Mihai Toma; Jacopo Aguzzi (Frontiers in Marine Science, 2022)
Behavioral rhythms are a key aspect of species fitness, since optimize ecological activities of animals in response to a constantly changing environment. Cabled observatories enable researchers to collect long-term biological and environmental data in real-time, providing relevant information on coastal fishes’ ecological niches and their temporal regulation (i.e., phenology). In this framework, the platform OBSEA (an EMSO Testing-Site in the NW coastal Mediterranean) was used to monitor the 24-h and seasonal occurrence of an ecologically iconic (i.e., top-predator) coastal fish species, the common dentex ( Dentex dentex ). By coupling image acquisition with oceanographic and meteorological data collection at a high-frequency (30 min), we compiled 8-years’ time-series of fish counts, showing daytime peaks by waveform analysis. Peaks of occurrence followed the photophase limits as an indication of photoperiodic regulation of behavior. At the same time, we evidenced a seasonal trend of counts variations under the form of significant major and minor increases in August and May, respectively. A progressive multiannual trend of counts increase was also evidenced in agreement with the NW Mediterranean expansion of the species. In GLM and GAM modeling, counts not only showed significant correlation with solar irradiance but also with water temperature and wind speed, providing hints on the species reaction to projected climate change scenarios. Grouping behavior was reported mostly at daytime. Results were discussed assuming a possible link between count patterns and behavioral activity, which may influence video observations at different temporal scales.

The EMSO Generic Instrument Module (EGIM): Standardized and Interoperable Instrumentation for Ocean Observation - Nadine Lantéri; Henry A. Ruhl; Andrew Gates; Enoc Martínez; Joaquin del Rio Fernandez; Jacopo Aguzzi; Mathilde Cannat; Eric Delory; Davide Embriaco; Robert Huber; Marjolaine Matabos; George Petihakis; et al. (Frontiers in Marine Science, 2022)
The oceans are a fundamental source for climate balance, sustainability of resources and life on Earth, therefore society has a strong and pressing interest in maintaining and, where possible, restoring the health of the marine ecosystems. Effective, integrated ocean observation is key to suggesting actions to reduce anthropogenic impact from coastal to deep-sea environments and address the main challenges of the 21st century, which are summarized in the UN Sustainable Development Goals and Blue Growth strategies. The European Multidisciplinary Seafloor and water column Observatory (EMSO), is a European Research Infrastructure Consortium (ERIC), with the aim of providing long-term observations via fixed-point ocean observatories in key environmental locations across European seas from the Arctic to the Black Sea. These may be supported by ship-based observations and autonomous systems such as gliders. In this paper, we present the EMSO Generic Instrument Module (EGIM), a deployment ready multi-sensor instrumentation module, designed to measure physical, biogeochemical, biological and ecosystem variables consistently, in a range of marine environments, over long periods of time. Here, we describe the system, features, configuration, operation and data management. We demonstrate, through a series of coastal and oceanic pilot experiments that the EGIM is a valuable standard ocean observation module, which can significantly improve the capacity of existing ocean observatories and provides the basis for new observatories. The diverse examples of use included the monitoring of fish activity response upon oceanographic variability, hydrothermal vent fluids and particle dispersion, passive acoustic monitoring of marine mammals and time series of environmental variation in the water column. With the EGIM available to all the EMSO Regional Facilities, EMSO will be reaching a milestone in standardization and interoperability, marking a key capability advancement in addressing issues of sustainability in resource and habitat management of the oceans.

Framing Cutting-Edge Integrative Deep-Sea Biodiversity Monitoring via Environmental DNA and Optoacoustic Augmented Infrastructures - Sergio Stefanni; Luca Mirimin; David Stanković; Damianos Chatzievangelou; Lucia Bongiorni; Simone Marini; Maria Vittoria Modica; Elisabetta Manea; Federico Bonofiglio; Joaquin del Rio Fernandez; Neven Cukrov; Ana Gavrilović; et al. (Frontiers in Marine Science, 2022)
Deep-sea ecosystems are reservoirs of biodiversity that are largely unexplored, but their exploration and biodiscovery are becoming a reality thanks to biotechnological advances (e.g., omics technologies) and their integration in an expanding network of marine infrastructures for the exploration of the seas, such as cabled observatories. While still in its infancy, the application of environmental DNA (eDNA) metabarcoding approaches is revolutionizing marine biodiversity monitoring capability. Indeed, the analysis of eDNA in conjunction with the collection of multidisciplinary optoacoustic and environmental data, can provide a more comprehensive monitoring of deep-sea biodiversity. Here, we describe the potential for acquiring eDNA as a core component for the expanding ecological monitoring capabilities through cabled observatories and their docked Internet Operated Vehicles (IOVs), such as crawlers. Furthermore, we provide a critical overview of four areas of development: (i) Integrating eDNA with optoacoustic imaging; (ii) Development of eDNA repositories and cross-linking with other biodiversity databases; (iii) Artificial Intelligence for eDNA analyses and integration with imaging data; and (iv) Benefits of eDNA augmented observatories for the conservation and sustainable management of deep-sea biodiversity. Finally, we discuss the technical limitations and recommendations for future eDNA monitoring of the deep-sea. It is hoped that this review will frame the future direction of an exciting journey of biodiscovery in remote and yet vulnerable areas of our planet, with the overall aim to understand deep-sea biodiversity and hence manage and protect vital marine resources.

Integrating Diel Vertical Migrations of Bioluminescent Deep Scattering Layers Into Monitoring Programs - Damianos Chatzievangelou; Nixon Bahamon; Séverine Martini; Joaquin del Rio; Giorgio Riccobene; Michael Tangherlini; Roberto Danovaro; Fabio C. De Leo; Benoit Pirenne; Jacopo Aguzzi (Frontiers in Marine Science, 2021)
The deep sea (i.e., >200 m depth) is a highly dynamic environment where benthic ecosystems are functionally and ecologically connected with the overlying water column and the surface. In the aphotic deep sea, organisms rely on external signals to synchronize their biological clocks. Apart from responding to cyclic hydrodynamic patterns and periodic fluctuations of variables such as temperature, salinity, phytopigments, and oxygen concentration, the arrival of migrators at depth on a 24-h basis (described as Diel Vertical Migrations; DVMs), and from well-lit surface and shallower waters, could represent a major response to a solar-based synchronization between the photic and aphotic realms. In addition to triggering the rhythmic behavioral responses of benthic species, DVMs supply food to deep seafloor communities through the active downward transport of carbon and nutrients. Bioluminescent species of the migrating deep scattering layers play a not yet quantified (but likely important) role in the benthopelagic coupling, raising the need to integrate the efficient detection and quantification of bioluminescence into large-scale monitoring programs. Here, we provide evidence in support of the benefits for quantifying and continuously monitoring bioluminescence in the deep sea. In particular, we recommend the integration of bioluminescence studies into long-term monitoring programs facilitated by deep-sea neutrino telescopes, which offer photon counting capability. Their Photo-Multiplier Tubes and other advanced optical sensors installed in neutrino telescope infrastructures can boost the study of bioluminescent DVMs in concert with acoustic backscatter and video imagery from ultra-low-light cameras. Such integration will enhance our ability to monitor proxies for the mass and energy transfer from the upper ocean into the deep-sea Benthic Boundary Layer (BBL), a key feature of the ocean biological pump and crucial for monitoring the effects of climate-change. In addition, it will allow for investigating the role of deep scattering DVMs in the behavioral responses, abundance and structure of deep-sea benthic communities. The proposed approach may represent a new frontier for the study and discovery of new, taxon-specific bioluminescence capabilities. It will thus help to expand our knowledge of poorly described deep-sea biodiversity inventories and further elucidate the connectivity between pelagic and benthic compartments in the deep-sea.

Allometry, Function and Shape Diversification in the Inner Ear of Platyrrhine Primates - Joaquin del Rio; Leandro Aristide; Sergio F. dos Reis; Thais M. P. dos Santos; Ricardo T. Lopes; S. Ivan Perez (Journal of Mammalian Evolution, 2021)

Toward a Comprehensive and Integrated Strategy of the European Marine Research Infrastructures for Ocean Observations - Juan Jose Dañobeitia; Sylvie Pouliquen; Truls Johannessen; Alberto Basset; Mathilde Cannat; Benjamin Gerrit Pfeil; Maria Incoronata Fredella; Paola Materia; Claire Gourcuff; Giuseppe Magnifico; Eric Delory; Joaquin del Rio Fernandez; et al. (Frontiers in Marine Science, 2020)

Ocean Data Product Integration Through Innovation-The Next Level of Data Interoperability - Justin J. H. Buck; Scott J. Bainbridge; Eugene F. Burger; Alexandra C. Kraberg; Matthew Casari; Kenneth S. Casey; Louise Darroch; Joaquin Del Rio; Katja Metfies; Eric Delory; Philipp F. Fischer; Thomas Gardner; et al. (Frontiers in Marine Science, 2019)

Sustained stress-induced changes in mice as a model for chronic depression - Natalia Elizalde; Alvaro L. García-García; Susan Totterdell; Nerea Gendive; Elisabet Venzala; Maria J. Ramirez; Joaquin Del Rio; Rosa M. Tordera (Psychopharmacology, 2010)